Coverage of endangered species in environmental risk assessments at EFSA. (3rd February 2016) - ,
Abstract: The EFSA performs environmental risk assessment (ERA) for single potential stressors such as plant protection products, genetically modified organisms and feed additives, and for invasive alien species that are harmful to plant health. This ERA focusses primarily on the use or spread of such potential stressors in an agricultural context, but also considers the impact on the wider environment. It is important to realise that the above potential stressors in most cases contribute a minor proportion of the total integrated pressure that ecosystems experience. The World Wildlife Fund listed the relative attribution of threats contributing to the declines in animal populations as follows: 37% from exploitation (fishing, hunting, etc.), 31% habitat degradation and change, 13% from habitat loss, 7% from climate change, and only 5% from invasive species, 4% from pollution and 2% from disease. In this scientific opinion, the Scientific Committee gathered scientific knowledge on the extent of coverage of endangered species in current ERA schemes that fall under the remit of EFSA. The legal basis and the relevant ecological and biological features used to classify a species as endangered are investigated. The characteristics that determine vulnerability of endangered species are reviewed. Whether endangered species are more at risk from exposure to potential stressors than other nontarget species is discussed, but specific protection goals for endangered species are not given. Due to a lack of effect and exposure data for the vast majority of endangered species, the reliability of using data from other species is a key issue for their ERA. This issue and other uncertainties are discussed when reviewing the coverage of endangered species in current ERA schemes. Potential tools, such as population and landscape modelling and trait‐based approaches, for extending the coverage of endangered species in current ERA schemes, are explored and reported.